Co-extraction of vanadium and chromium from high chromium containing vanadium slag by low-pressure liquid phase oxidation method. (1st December 2018) - Wu, Kanghua; Wang, Yaru; Wang, Xinran; Wang, Shaona; Liu, Biao; Zhang, Yi; Du, Hao
Abstract: High chromium containing vanadium slag is refractory, and therefore cannot be processed efficiently by traditional roasting method. In this study, a low pressure leaching process using NaOH solution to co-extract both vanadium and chromium has been proposed. The effects of NaOH concentration, leaching temperature, oxygen pressure, and liquid-to-solid mass ratio on the vanadium and chromium leaching rate were discussed in detail. The results suggested that the NaOH concentration and leaching temperature were more influential factors for the extraction of vanadium and chromium. Under the optimal reaction conditions (temperature 200 °C, liquid-to-solid mass ratio of 6:1, NaOH mass concentration of 50%, agitation speed 700 rpm, pressure of 1 MPa, and reaction time 180 min), the recoveries of vanadium and chromium could reach up to 98.3% and 93.3%, respectively. The kinetics study indicated that the dissolution process of vanadium slag followed the shrinking core model, and the extraction of vanadium and chromium were both governed by the internal diffusion control. Furthermore, the apparent activation energies for the oxidation of vanadium and chromium were calculated to be 27.58 and 36.74 kJ/mol, respectively. The result from this study provides insights on effectively co-extracting V and Cr from high Cr-containing vanadium slag while minimizing the environmental contamination. Highlights: A clean leaching process has been developed to co-extract both V and Cr. Optimized leaching rate is identified to be 98.3 and 93.3% for V and Cr. The effects of reaction parameters on the V and Cr leaching rate were discussed. The leaching kinetics for co-extraction of both V and Cr have been investigated.